PENGARUH PROFITABILITAS, LEVERAGE DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2016 – 2021) - Hotnida Sari Tanjung; Novera Martilova (Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine and analyze how much influence changes in Profitability, Leverage, and Institutional Ownership have on Earnings Management in manufacturing companies listed on the Indonesia Stock Exchange for the 2016- 2021 period. This type of research is quantitative research, the type of data is secondary data accessed through the official website of the Indonesia Stock Exchange (www.idx.co.id). The sample for this research was taken from 10 manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2021 period using a purposive sampling technique. The method used in this study uses the classical assumption test, multiple linear regression analysis, coefficient of determination test, and hypothesis testing. The results of this study partially show that profitability has no significant effect on earnings management as evidenced by the significant level of variables in the t test which shows tcount<ttable (0.391 <2.003). Leverage has no significant effect on earnings management which can be seen from the results of the t test which shows tcount<ttable (1.837 <2.003) and institutional ownership also has no significant effect on earnings management which shows tcount<ttable (-1.006 <2.003). Profitability, Leverage, and Institutional Ownership have no significant effect on earnings management. This can be seen from the results of the hypothesis test which show a significant value of 0.240 > 0.05 and the comparison of fcount<ftable (1.444 <2.77) means that Ha is rejected.